KEGIATAN PENDIDIKAN: SOSIALISASI, PENGUATAN, SKRINING DAN PELATIHAN KETERAMPILAN DALAM PENCEGAHAN TINDAK PIDANA PERDAGANGAN ORANG PADA MASYARAKAT URBAN KOTA DENPASAR - NLP Yunianti Suntari; A. A Sri Wahyuni (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2020)
Background : Tourism in Bali is also followed by positive and negative impacts on the Balinese people. The positive impact is such as the large number of jobs that are able to absorb labor, while the negative impact is the emergence of social issues such as human trafficking which can threaten the young generation of Bali. Method : Activities by providing education about human trafficking. And provide life skills training. Target adolescents, both those who attend school and drop out of school. Result : Lentera Anak Bali (LAB) is an independent non-profit organization engaged in child protection to obtain their rights. LAB sees the importance of these children’s problems by involving the local government, social services, education offices, health offices and community leaders. In an effort to build awareness of the vulnerability of these children and make preventive education efforts against the possibility of being caught in human trafficking,by conducting outreach to officials, the caring community, and the youth themselves.These adolescents are given education on safe life skills (free of prostitution),understanding of human trafficking, education on health and welfare, and examination of reproductive organs. With this facilitation, it is hoped that they can protect themselves and become counselors for their teenage friends. Conclusion : this activity can increase public understanding of the danger of human trafficking. (1) There is a group of young urban workers who receive assistance from the human trafficking prevention team. (2) Youth groups who received training on safe life skills (prostitution free), understanding of human trafficking, health education, and examination of reproductive organs.